The merged African Court of Justice and Human Rights (ACJ&HR) as a better criminal justice system than the ICC: Are we Finding African Solution to African problems or creating African problems without solutions? - Harrison Otieno, Mbori (University of Nairobi Law Journal, 2015)
A completely new creature unprecedented before in international law is emerging in Africa. The African Court of Justice and Human Rights (ACJHR) (herein after referred to as the Merged Court) will also have a criminal chamber to try international crimes. The mandate of the court will be tripartite and this article seeks to analyse this latest facet; the introduction of an international criminal chamber. Expansion of the jurisdiction of the ACJHR will see the merger of state-level and individual- level criminal accountability mechanism for human rights violations on an international scale.1 The infraction between the African Union (AU) and the International Criminal Court (ICC),2 was arguably warranted by the latter’s issuance of arrest warrants against sitting African heads of state and senior government officials.3 These developments induced the AU to take ‘retaliatory’ measures which culminated in conferring international criminal jurisdiction on its court.4
Keywords: African Court of Justice; Human Rights; Criminal Justice System; ICC